Genesis of As in the groundwater with extremely high salinity in the Yellow River Delta, China. (April 2022) - Zhi, Chuanshun; Cao, Wengeng; Wang, Zhen; Li, Zeyan; Ren, Yu
Abstract: High arsenic (As) groundwater has been extensively found in river delta worldwide, but understanding of the influence of high salinity on As mobilization remains limited. Therefore, this study took the Yellow River Delta as the study area and tested an alternative method–ionic ratios to explore the hydrogeochemical processes of high As groundwater. Eighty–one groundwater samples and three river water samples were collected for chemical analysis. Based on inflection points of HCO3 /Cl, Na/Cl, and SO4 /Cl cumulative frequency distribution and hydrogeological conditions, three hydrogeochemical zones have been determined: Weathering–Fresh Water Zone (Zone I), Evaporation–Saline Water Zone (Zone II), and Seawater Mixing–Reduction Zone (Zone III). Concentrations of As and total dissolved solids (TDS) showed an increasing trend in groundwater from Zone I to Zone III. Zone I groundwater with low As and low TDS was mainly controlled by rock weathering and strong flushing. Due to intensive evaporation and seawater mixing, the TDS concentration in the groundwater of Zone II and Zone III increased sharply (up to 145997 mg/L). The high As groundwater in Zone II and Zone III was characterized by high Fe 2+ and NH4 + and low NO3 − and SO4 /Cl, indicating that reductive dissolution of As–bearing iron oxides is the key process for As release. In addition, the significantly positive correlation between As and Cl − (>10000 mg/L) under different pH conditions indicated that intensive salinization may contribute to As mobility. Results of cluster analysis revealed that reductive dissolution is the principal driving force for As release in coastal groundwater systems and salinization is the secondary one. Graphical abstract: Image 1 Highlights: HCO3 /Cl, Na/Cl, and SO4 /Cl ratios were used to identify hydrogeochemical zonation. Elevated As in groundwater co-occurred with high salinity. Arsenic release is mainly caused by reductive dissolution of iron oxides, followed by salinization. Extremely high salinity (high Cl − ) may promote As desorption in groundwater under reducing environment.